Measuring Teachers' Intervention Fidelity. (November 2018) - King-Sears, Margaret E.; Walker, Jennifer D.; Barry, Colleen
School personnel implementing interventions new or unfamiliar to them need to know how to implement the intervention with fidelity. A five-step process is described that can be used to design and implement fidelity procedures with teachers using new or unfamiliar interventions.